Correlation of the ECG changes (ST segment depression with or without T wave inversion in lateral leads 1, avl. V4-V6) with coronary angiographic findings in ACS patients (University Heart Journal, 2014)
No Abstract Available.DOI: http://dx.doi.org/10.3329/uhj.v9i1.19431 University Heart Journal Vol. 9, No. 1, January 2013; 9-12